All-trans retinoic acid and arsenic trioxide induce apoptosis and modulate intracellular concentrations of calcium in hepatocellular carcinoma cells. (December 2014) - Wei, Jianfeng; Ye, Chaoping; Liu, Fengsheng; Wang, Wenqing
<x content-type="archive" xml:space="preserve">Abstract</x> We investigated the effects of all-trans retinoic acid (ATRA) and arsenic trioxide (ATO), alone and in combination, on apoptosis and intracellular calcium concentration in hepatocellular carcinoma (HepG2) cells. We used HepG2 cells to test the effects of ATRA and ATO, individually and in combination, on cell proliferation, apoptosis, and intracellular-free calcium concentration. The results indicate that each drug decreased cell proliferation, increased apoptosis, and increased intracellular-free calcium in a time- and dose-dependent manner. We also calculated the coefficients of drug interaction for sub-threshold administration of both drugs in combination (1 μmol/L each). ATRA and ATO acted synergistically in inhibition of cell proliferation and additively in the promotion of apoptosis. All-trans retinoic acid and ATO interacted synergistically to reduce cell proliferation in HepG2 cells.